Comparative study on the novel umami‐active peptides of the whole soybeans and the defatted soybeans fermented soy sauce. (12th August 2020) - Zhu, Xiping; Sun‐Waterhouse, Dongxiao; Chen, Jiahui; Cui, Chun; Wang, Wei
Abstract: BACKGROUND: Two kinds of soy sauce produced via fermentation of the whole soybeans and the defatted soybeans (soy sauce termed 'SSS' and 'SSD', respectively) were subjected to the treatment using aqueous ethanol solutions with high concentrations. Then tasty peptides were separated from SSS and SSD by sensory guided fractionation, using macroporous resin and reverse‐phase high‐performance liquid chromatography (RP‐HPLC), and identified by ultra‐performance liquid chromatography quadrupole time‐of‐flight tandem mass spectrometry (UPLC‐Q‐TOF‐MS/MS). Results: The result showed that umami‐active fractions and ≤ 3 kDa peptides were mainly concentrated in the supernatants resulted from the treatment with 60% ethanol and the precipitates resulted from the treatment with 80% ethanol. The contents of ammonia nitrogen, non‐salt solids, bitter amino acids, amino acids in peptides and the proportion of ≤ 3 kDa peptides in SSS were higher than those in SSD. Sixteen and fourteen tasty peptides were separated from SSS and SSD, among them five dipeptides (γ‐Glu‐Glu, Glu‐Glu, γ‐Glu‐Cys, γ‐Glu‐Leu, Glu‐Leu and Ile‐Glu) with a glutamic acid residue were identified both in SSS and SSD, which have been reported as umami/kokumi‐active peptides in soy sauce. Several peptides identified from SSS (Thr‐Gly‐Cys, Gly‐Leu‐Glu, Val‐Glu‐Ala‐Leu and Gly‐Gly‐Gly‐Glu) and SSD (Asp‐Arg, Asp‐Ala‐Glu, Glu‐Val‐Cys and Gly‐Gly‐Gly‐Glu) are tasty and/or umami‐active peptides but have not been reported as tasty peptides in the past. Conclusion: Most of the peptides separated from SSD and SSS could impart an umami‐enhancing effect on soy sauce, and the marginally more kokumi and bitterness hydrophobic peptides were found in SSS than SSD. © 2020 Society of Chemical Industry